Unequal opportunities and human capital formation - Daniel Mejίa; Marc St-Pierre (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper develops a tractable, heterogeneous agents general equilibrium model where individuals have different endowments of the factors that complement the schooling process. The paper explores the relationship between inequality of opportunities, inequality of outcomes, and efficiency in human capital formation. Using numerical solutions we study how the endogenous variables of the model respond to two different interventions in the distribution of opportunities: a mean-preserving spread and a change in the support. The results suggest that a higher degree of inequality of opportunities is associated with lower average level of human capital, a lower fraction of individuals investing in human capital, higher inequality in the distribution of human capital, and higher wage inequality. In other words, the model does not predict a trade-off between efficiency and equality of opportunity in human capital formation.
Keywords: J31; J24; D33; O15; 330; human capital; inequality; equity-efficiency trade-off; Bildungsinvestition; Bildungschancen; Bildungsverhalten; Bildungspolitik; Wirtschaftliche Effizienz; Allgemeines Gleichgewicht; Theorie